CONNECTING CONTEXTUAL PERFORMANCE TO CULTURAL OPENNESS, STRATEGIC MANAGEMENT, AND ORGANIZATIONAL CLIMATE THROUGH INNOVATIVE WORK BEHAVIOR: EVIDENCE FROM PRIVATE UNIVERSITIES - Supriadi, Supriadi; Abdrazakova, Ainur; Listyaningsih, Erna (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Supportive organizational climates and strategic management that prioritizes innovation are critical variables that affect contextual performance. Nevertheless, this influence is not directly felt; rather, it is facilitated by innovative work practices. People who are motivated by the company's strategy and supported by a positive organizational climate are more likely to demonstrate innovative work behavior, which in turn enhances their contextual performance and makes a positive contribution to the organization as a whole. The sample for this study was composed of 280 educational staff members from nine private universities in Medan City, each of which had a minimum accreditation rating of B. Descriptive and structural equation modeling (SEM) analyses were implemented. It is evident from the findings that innovative work behavior is significantly influenced by cultural openness. Work behavior that is innovative has a substantial impact on contextual performance. The influence of cultural openness and contextual performance is mediated by innovative work behavior. The behavior of innovative employees is substantially determined by strategic management. Contextual performance is substantially predicted by strategic management. The influence of strategic management and contextual performance is mediated by innovative work behavior. Innovative work behavior is substantially determined by organizational climate. The contextual performance is significantly influenced by the organizational climate. Innovative work behavior serves as a mediator between contextual performance and organizational climate.